2017
DOI: 10.18355/pg.2017.6.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Activities Led in the Romance Languages Intelligibility Perspective

Abstract: In this paper, we highlight the contribution in the development of plurilingual intercultural competence through learning multiple languages from one language branch -Romance languages. Activities which are the focus of attention of the sampled students are only exploratory. Nevertheless, we motivated students who do not speak more Roman languages to learn these languages simultaneously. We were able to raise their interest and motivation. Within the second activity we have proved that also the literary text m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Dixson (1991) found out that while listening, anxious students had difficulty to comprehend the content of the target language. Zhai (2015) stated significant negative correlation between FLA and listening comprehension and put forward some useful suggestions to enhance listening proficiency of foreign language learners (Birova, Mockova, Simkova, Kralova, Lipkova, 2017). Sellers (2000) investigated the relationship between anxiety and reading and concluded that anxious students do not understand the tasks correctly and tend to recall less passage content while reading than their less anxious mates.…”
Section: Skills-based Foreign Language Anxietymentioning
confidence: 99%
“…Dixson (1991) found out that while listening, anxious students had difficulty to comprehend the content of the target language. Zhai (2015) stated significant negative correlation between FLA and listening comprehension and put forward some useful suggestions to enhance listening proficiency of foreign language learners (Birova, Mockova, Simkova, Kralova, Lipkova, 2017). Sellers (2000) investigated the relationship between anxiety and reading and concluded that anxious students do not understand the tasks correctly and tend to recall less passage content while reading than their less anxious mates.…”
Section: Skills-based Foreign Language Anxietymentioning
confidence: 99%